Hebrew Science in Early Medieval South Italy: Greco-Latin Astrological Lore in Hebrew Garb - Mancuso, Piergabriele (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2013)
Scienza ebraica nell'Italia meridionale dell'Alto Medioevo: tradizioni astrologiche greco-latine in veste ebraica Nel contributo si presenta un esame preliminare del ruolo del greco e del latino nella formazione del lessico astronomico e astrologico ebraico. L'analisi compiuta su varie opere ebraiche composte nell'Italia meridionale nell'Alto Medioevo rivela, fra l'altro, come parte della terminologia normalmente attribuita ad astronomi/astrologi del XII-XIII secolo (per esempio, Avraham ibn Ezra), risalga in realtà a studiosi del periodo altomedievale, le cui opere erano caratterizzate da un'alta interazione fra la tradizione greca e quella ebraica. Nell'articolo si prendono in esame, in particolar modo, i testi di Šabbetay Donnolo, uno dei principali intellettuali ebrei del X secolo. Hebrew Science in Early Medieval South Italy: Greco-Latin Astrological Lore in Hebrew Garb The aim of this paper is to offer a preliminary examination of the extent to which Latin and Greek have contributed to the creation of an astrological Hebrew terminology. Author's analysis of Hebrew astrological texts composed or known to early medieval southern Italy, revealed some unexpected information, such as, for example, that some of the advancements – specifically those in terminology – commonly attributed to 12th and 13th century Jewish astrologers (for example, to Avraham Ibn Ezra), were in fact made possible thanks to the work of early medieval scholars and interactions between Jewish and Graeco-Latin traditions. In this paper it is examined a series of works composed around the 10th century by southern Italian Jewish astrologers. Most of these texts are by Shabbatai Donnolo, one of the most important intellectuals of Jewish Apulia.